The RAFT copolymerization of acrylic acid and acrylamide. (19th August 2016) - Capasso Palmiero, Umberto; Chovancová, Anna; Cuccato, Danilo; Storti, Giuseppe; Lacík, Igor; Moscatelli, Davide
Abstract: The reversible addition-fragmentation chain transfer (RAFT) copolymerization of non-ionized acrylic acid with acrylamide in dimethyl sulfoxide is investigated and compared with the conventional free radical process carried out at the same conditions. The effect of the living nature of the RAFT process on overall polymerization rate and on copolymer composition is studied by in situ 1 H NMR. The same values of reactivity ratios (r AA = 1.55 ± 0.02 and r Am = 0.75 ± 0.02) are estimated for both the processes, living and non-living. The copolymers prepared by RAFT polymerization exhibit well-controlled composition, with narrow distribution. This approach can be applied to the synthesis of copolymer standards at specific composition for direct calibration of size-exclusion chromatography. Graphical abstract: Highlights: The impact of the backbiting reactions is reduced in the RAFT copolymerization. The composition drift is independent of the amount of the RAFT agent. The reactivity ratios for RAFT and free radical copolymerization are the same.